Hypodermoclysis in cancer patients in palliative care - Gislene Pontalti; Caren de Oliveira Riboldi; Luciana dos Santos; Vanessa Kenne Longaray; Desirée Amorim Guzzo; Isabel Cristina Echer (Universidade Federal de Santa Maria, 2018)
Aim: to analyze the use of hypodermoclysis in cancer patients in palliative care. Method: descriptive, cross - sectional study, with the purpose of describing the experience in patients undergoing palliative care, performed at a university hospital in southern Brazil. The sample consisted of 80 patients hospitalized in palliative care between March 2014 and March 2015. The data collection was made by specific instrument and the analysis was made through descriptive statistics. Results: pancreas 9 (11.3%), intestine 8 (10%), lung 8 (10%) and gastric 8 (10%) were the predominant neoplasms. Among the indications for hypodermoclysis, there were analgesia 63 (78.8%), precarious venous network 51 (63.8%) and oral intolerance 38 (47.5%). Of the 21 drugs prescribed and administered, the following stand out: morphine 76 (95.0%), metoclopramide 49 (61.3%), dipyrone 39 (48.8%), ondansetron 29 (36.3%) and dexamethasone 12 (15,0%). There were 105 punctures and no systemic complications. Final considerations: hypodermoclysis has been shown to be an effective, safe and less invasive drug combination in palliative clinical practice.